Evaluation of root and root canal morphology of mandibular and maxillary canine teeth in Turkish subpopulation by cone beam computed tomography with using two classification systems - Guldane Magat; Sultan Uzun (BMC Oral Health)
Abstract Background Knowledge of root and canal morphology is a prerequisite for effective nonsurgical and surgical endodontic treatments. The aim of this cone beam computed tomography (CBCT) study was to evaluate the root canal morphology of permanent canines in a Turkish subpopulation using two classification systems. Methods A total of 2,000 canine teeth were examined. The number of roots was identified, and root canal configurations were classified according to Vertucci’s classification and a new system for classifying root and canal morphology. Fisher’s exact test was used for statistical analysis, and the level of significance was set at 0.05 (p = 0.05). Results The canal configuration type I was the most common in all canines, while type III was the second most common. According to the new system, the code 1C1−1 was the most common, whilst 1C1 (A1) codes were the second most common for all canines. In this study, more than 10% morphology that did not fit the Vertucci classification was detected. In the categorization of accessory canals based on the new classification, the most common type in all canines was 1C1,1 (A1). Age had an effect only on the morphology of the left maxillary canine (p < 0.05). Conclusion Canines in the Turkish subpopulation showed a relatively high degree of variation in root and canal anatomical variations. Clinicians should be aware of where canals converge or diverge to avoid missing canals. The new system for classifying canal morphology describes root and canal configurations more accurately and practically compared to the Vertucci classification.